Multi‐Omics Profiling for NF1 Target Discovery in Neurofibromin (NF1) Deficient Cells. Issue 11 (31st May 2019) - Carnes, Rachel M.; Mobley, James A.; Crossman, David K.; Liu, Hui; Korf, Bruce R.; Kesterson, Robert A.; Wallis, Deeann
Abstract: Loss of NF1 is an oncogenic driver. In efforts to define pathways responsible for the development of neurofibromas and other cancers, transcriptomic and proteomic changes are evaluated in a non‐malignant NF1 null cell line. NF1 null HEK293 cells were created using CRISPR/Cas9 technology and they are compared to parental cells that express neurofibromin. A total of 1222 genes and 132 proteins are found to be differentially expressed. The analysis is integrated to identify eight transcripts/proteins that are differentially regulated in both analyses. Metacore Pathway analysis identifies Neurogenesis NGF/TrkA MAPK‐mediated signaling alterations. Next, the data set is compared with other published studies that involve analysis of cells or tumors deficient for NF1 and it is found that 141 genes recur in the sample and others; only thirteen of these genes recur in two or more studies. Genes/proteins of interest are validated via q‐RT‐PCR or Western blot. It is shown that KRT8 and 14‐3‐3σ protein levels respond to exogenously introduced mNf1 cDNA. Hence, transcripts/proteins that respond to neurofibromin levels are identified and they can potentially be used as biomarkers.